2022
DOI: 10.1177/09564624221091752
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to receive COVID-19 vaccination in people living with HIV/AIDS from Latin America

Abstract: Background Prior research has established some risk factors for an increased risk of severe disease and mortality from coronavirus disease 2019 (COVID-19). However, the impact of HIV infection on SARS-CoV-2 susceptibility and severity is a significant gap in the literature. In the same way, not many studies across the globe have analyzed the degree of vaccination willingness among people living with HIV/AIDS (PLWHA) and considerations regarding prioritizing this population during vaccination plans, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…In two (14.29%) studies, all included HIV patients were on ART [21,26]; in nine (64.29%) studies, the percentage of PLHIV on ART ranged between 59.3% and 98% [23,28] and the remaining three (21.42%) studies did not mention the ART status of participants [29][30][31]. The prevalence of COVID-19 vaccination ranged from 33.7% [28] to 87.1% [25] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In two (14.29%) studies, all included HIV patients were on ART [21,26]; in nine (64.29%) studies, the percentage of PLHIV on ART ranged between 59.3% and 98% [23,28] and the remaining three (21.42%) studies did not mention the ART status of participants [29][30][31]. The prevalence of COVID-19 vaccination ranged from 33.7% [28] to 87.1% [25] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…These reasons have also been reported as the major reasons for hesitancy among PLHIV in previous studies. [24] , [55] , [56] Multivariable analysis in other studies also showed these factors to be independently associated with higher odds of hesitancy towards the COVID-19 vaccine. [10] , [12] , [21] , [51] , [57] , [58] The fact that these concerns have been vastly reported across several studies indicates a lack of public awareness about the proven safety and efficacy profile of the COVID-19 vaccine, [59] not only among the general population but also among PLHIV, who may even have a greater degree of routine contact with healthcare professionals than the general population.…”
Section: Discussionmentioning
confidence: 79%
“…However, two studies conducted in China [15 ▪ ,16 ▪ ] found that younger PLWH were more likely to be vaccinated compared with their older counterparts. Other studies examining age did not find any statistically significant differences in vaccine uptake and acceptance [14 ▪ ,26 ▪▪ ,42 ▪▪ –45 ▪▪ ,48 ▪ ,50 ▪ ,51 ▪ ], demonstrating the need for further research, especially across different countries and contexts.…”
Section: Factors Associated With Vaccine Acceptance and Uptakementioning
confidence: 84%
“…Across a multitude of studies, participants have indicated concerns related to safety, efficacy and the overall development of COVID-19 vaccines as reasons for delaying or not receiving vaccines [14 ▪ ,26 ▪▪ ,41,42 ▪▪ –45 ▪▪ ]. Potential side effects and safety concerns have been reported as significant elements of COVID-19 vaccine hesitancy [43 ▪▪ ,45 ▪▪ ]. These concerns are related to the spread of misinformation and mistrust in the healthcare system fuelled by global political polarization.…”
Section: Factors Associated With Vaccine Hesitancymentioning
confidence: 99%
See 1 more Smart Citation